Prospects for using herbal preparation in combination with physical methods in complex therapy of chronic adenoiditis - M. Yu. Korkmazov (Медицинский совет, 2021)
Introduction. Importance of the search effective methods of treating chronic adenoiditis in children is associated with a high incidence and risk of developing complications. Treatment of chronic adenoiditis are described in the literature, but the advantages of any of them are inconclusive, which leads to the search for additional more progressive methods.Objective. To increase the effectiveness of the treatment of chronic adenoiditis using complex therapy of non-drug methods in combination with the herbal preparation Tonsilgon N.Materials and methods. Biochemical changes in lymphoid tissue were studied on biopsy material in 111 children with chronic adenoiditis, grade 3 adenoid hypertrophy, directed to planned surgical treatment. In the preoperative period, patients were divided into 4 groups: Group 1-control group, patients who received conventional methods of treatment; 2-study group, patients who additionally used low-frequency ultrasound irrigation of the nasal cavity and nasopharynx with photochromotherapy; The third group, patients who received the herbal preparation tonsilgon N (drops) as preoperative therapy; The fourth group study underwent low-frequency ultrasound irrigation of the nasal cavity and nasopharynx in combination with photochromotherapy and took the drug Tonsilgon N in an age-related dosage.Results and discussion. When comparing the results of biochemical studies, an increase in the products of lipid peroxidation was noted in patients of the first group, which was regarded as a factor in the protracted course of the disease. The use of targeted phytoniring drugs in combination with low-frequency ultrasonic cavitation and photochromotherapy in complex therapy significantly modulates the processes of lipid peroxidation and can potentiate the antioxidant protection of cells.Conclusion. Objective data were obtained for the first time on biochemical changes in lymphoid tissue for various methods of therapy indicate the prospects of using non-drug methods in combination with a herbal preparation in the complex therapy of chronic adenoiditis.